Skull Ossification in the Andean Toad Rhinella spinulosa (Bufonidae) and the Genetic Model Organism Xenopus tropicalis (Pipidae) Reveals Heterochrony Phenomena and Frontoparietal Suture Modifications - Mundaca, Marco; Rojas, Japhet; Cumilaf, Lefney; Jara, Federico; Munoz, David; Pastenes, Luis; Mendez, Marco; Tovar, Lina M.; Torrejon, Marcela; Montoya-Sanhueza, German; Marcellini, Sylvain (My University, 2024)
Anurans are famous for having evolved a highly simplified skull through bone loss and fusion events. Nevertheless, their skeleton displays a rich morphological diversity associated with adaptations to diverse lifestyles and ecological niches. Here, we report larval skull ossification in the Andean toad Rhinella spinulosa (Bufonidae), and compare it to the phylogenetically distant genetic model organism Xenopus tropicalis (Pipidae). We find that the ossification timing of most skull bones is conserved between both species, except for the prootic and the angulosplenial that ossify at much later stages in R. spinulosa than X. tropicalis. We propose that a delayed lower jaw ossification in R. spinulosa is tightly related to the more extensive metamorphosis process observed in this species where the ventrally oriented mouth opening shifts anteriorly. We also report two conspicuous notches in the R. spinulosa frontoparietal bone mineralization front which are absent in X. tropicalis, and presumably represent evolutionary remnants of the coronal suture that separates the frontal and parietal bones in most vertebrates. As such notches have not been overtly reported in the literature, we examined the X. tropicalis sibling species Xenopus laevis, and were able to identify similar, albeit transient, indentations in the forming frontoparietal bone, suggesting that vestigial coronal sutures might exist in more frog species than anticipated. Taken together, we show that R. spinulosa represents an ideal organism to study heterochronic shifts and the mechanisms underlying cranial suture loss which drove anuran skull simplification.
Keywords: andean toad; heterochrony; rhinella spinulosa; skull ossification; suture loss; xenopus tropicalis